PERENCANAAN DAN PENGADAAN OBAT DI PUSKESMAS SURABAYA TIMUR DAN SELATAN - Athijah, Umi; Zairina, Elida; Sukorini, Anila Impian; Rosita, Efrita Mega; Putri, Anindita Pratama (Indonesian Research Gateway)
Primary Health Center as an organization of public health service has an excellent service quality character, besides qualified medical services. Service will run if the availability and quality of medicines is assured. This study was conducted to get an overview of planning and procurement of medicines at primary health centers. It was observational and descriptive study. The sample was the entire primary health centers in South and East Surabaya (n = 26) and the respondent was the staff of primary health center who manage planning and procurement of medicines. The data was collected by validated questionnaires and check list. Results showed that 57.7% respondents was pharmacists. Non-DOEN generic medicines and patent medicines were provided by 61.5%. The combined method (epidemiology-consumption method) was used by 61.5% staff to calculate the medicine need. The unschedule procurements have been reported by 57.7% respondents.